MANAJEMEN RISIKO OLEH DINAS PU BINA MARGA KABUPATEN SIDOARJO DALAM MENANGANI GENANGAN DI KAWASAN BRINGIN KULON KECAMATAN TAMAN - Junita Risma Wanti; Binti Azizatun Nafi'ah (Journal Publicuho, 2025)
While the inundation has affected the daily lives of the residents, showing that there's always room for improvement, it has also highlighted the importance of proactive risk management in dealing with natural disasters. This provides an ideal opportunity to enhance risk management and ensure that similar issues don't arise in the future. This research aims to evaluate the effectiveness of the inundation management strategies implemented by the government and the local community. To achieve this, we are conducting a descriptive study. The collaborative efforts of various public organizations, including the Regency BPBD, Provincial BPBD, Public Works Office of Bina Marga and Water Resources of Sidoarjo Regency, village officials, sub-districts, and Koramil, are a testament to the commitment to tackle this challenge. The community's active involvement is crucial for the success of these efforts. The Bringin Kulon area's comprehensive approach to inundation management includes normalizing water pumps, cleaning water hyacinth and sediment, and installing floodgates. The risk management strategy, though time-consuming, is proving to be highly effective. The community's involvement, though limited, is crucial for the success of these efforts.